Government Spending and Inflationary Finance : A Public Finance Approach. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes the relationship between inflation tax and the level of government spending in a public finance context. The key feature of the model developed is that it recognizes the possibility that conventional taxes, such as the consumption tax, may carry increasing marginal collection costs. As a result, and unlike previous findings in the literature, the inflation tax becomes an increasing function of government spending. Furthermore, the more inefficient the tax collection system, the larger the increase in the inflation tax for a given increase in government spending. A numerical analysis of the model provides additional insights into these relationships.